Ghana - Meeting the Challenge of Accelerated and Shared Growth : Country Economic Memorandum, Volume 3. Background papers - World Bank (Washington, DC, 2012)
Ghana has done increasingly well in recent years. This report has analyzed these issues in considerable depth, making it a prime reference on Ghana's growth and poverty experience and current policy challenges. The Ghana Country Economic Memorandum (CEM) report presented in these three volumes brings together detailed, relevant analyses of Ghana's growth and the Millennium Development Goals (MDGs), poverty reduction, infrastructure, agriculture, investment climate, export competitiveness, social inclusion and political economy.